Minerais indicadores kimberlíticos e prospectividade diamantífera da intrusão alfeu-01 (canguçu, RS) - Chaves, Mario Luiz De Sá Carneiro; Andrade, Kerley Wanderson; Azzi, Andrezza De Assis [UNESP]; Silveira, Francisco Valdir (My University, 2014)
The Alfeu-01 kimberlite intrusion was discovered in 1994, and is hosted by granitoid rocks of the Pinheiro Machado Complex, of Neoproterozoic age, in the Sul-Riograndense shield. This kimberlite is melanocratic, and has an afanitic matrix where xenoliths of the host rocks as well as macrocrysts of phlogopite, rutil, garnet and, possibly diopside can be observed. The petrographic descriptions (basically phlogopite + olivine + talc + serpentine) indicate that it is an explosive breccia, probably of diatreme facies. In geochemical terms, the high contents of TiO2, MnO and K2O are characteristics, in contrast with diamondiferous intrusions of Minas Gerais. The garnets were divided into three different colors, a strong association of colors with the Fe2O3, MgO and Cr2O3contents having been observed. All garnets, identified as the pyrope type, are located in the mineral fields known as G4, G5 and G9, generally not associated to fertile intrusions. In the same way, the high oxidation grade in the Mg-ilmenite is not favorable for diamond preservation. Chromite data indicates that the mineral is out of the diamond inclusion field. Diopside of the intrusion is Cr-poor, and recognized as associated to an alkaline basalt suite. All mineralogical parameters characteristically diverge from the observed in fertile kimberlites of Minas Gerais; in this way, they strongly not encourage another prospecting works on the intrusion.
Minerals and indicators kimberlite diamond prospectivity the intrusion alpheus-01 (Canguçu, RS)
Keywords: Indicator minerals; Kimberlite; Sul-Riograndense shield